Effectiveness of cognitive-behavioral therapy (CBT) in improving the quality of life and psychological fatigue in women with polycystic ovarian syndrome: a randomized controlled clinical trial - Leila Abdollahi; Mojgan Mirghafourvand; Jalil Kheyradin Babapour; Mozhdeh Mohammadi (Taylor & Francis Group, 2019)
Introduction: Given the increasing prevalence of complications caused by the polycystic ovarian syndrome (PCOS) such as medical and psychological problems and also the chronicity of this disease, patients with the PCOS tend to experience lower quality of life and greater psychological fatigue similar to other patients with chronic diseases. This study was conducted to determine the effects of cognitive-behavioral therapy (CBT) on the quality of life and psychological fatigue in women with the PCOS. Methods: This randomized controlled clinical trial study, conducted from 2016 to 2017, enrolled 74 women aged between 18 and 35 years from the Iranian city of Saqqez. The participants were assigned to a CBT group and a control group via block randomization. The intervention group received 8 weekly CBT sessions between 45 and 60 minutes each. The Polycystic Ovary Syndrome Health-Related Quality of Life Questionnaire (PCOSQ) and the Fatigue Impact Scale (FIS) were completed by the patients before and after the intervention. Results: No significant differences were observed between the two groups before the intervention in terms of sociodemographic characteristics and the mean scores of quality of life and psychological fatigue. After the intervention, the mean (standard deviation [SD]) of the quality of life score was 60.2 (13.3) in the intervention group and 24.4 (15) in the control group, with the mean score of quality of life being significantly higher in the intervention group than in the control group (adjusted mean difference = 33.1). The mean (SD) score of psychological fatigue was 28.2 (13.9) in the intervention group and 78.2 (37.1) in the control group, with the mean score of psychological fatigue being significantly lower in the intervention group than in the control group (−54.8). Conclusions: The results showed that CBT was able to reduce fatigue and improve quality of life in our sample of women with the PCOS and ultimately boost their health.